More Than Words: Outlining Preconditions to Collaboration Among First Nations, the Federal Government, and the Provincial Government - Lachance, Nathalie; Rose, Teresa (The International Indigenous Policy Journal, 2020)
Since 2015, there has been heightened interest in reconciliation and renewed relationships with Indigenous Peoples. Anchoring our work in the definition of reconciliation provided by the Truth and Reconciliation Commission of Canada, we, as practitioner-scholars, sought to better understand the preconditions to collaboration among First Nations, the federal government, and the provincial government in Alberta. This participatory action research was conducted with mid- to senior-level public servants, who were involved in the further development and implementation of the 2014 Joint Action Plan to Improve the Health of First Nations in Alberta, in either First Nations, the federal government, or the provincial government. This article concludes that collaboration must consider the negative legacy of relationships between First Nations and federal and provincial governments, as well as between First Nations and settlers.